Mathematical Literacy Research in Mathematics Learning: Bibliometric Review - Maharani, Swasti; Hendrisa Rizqie Romandoni; Tiara Citra Maharani Firdaus; Muhammad Noor Kholid; Widia Yunita (Cita Konsultindo Research Center, 2024)
This study aims to identify and analyze publications related to mathematical literacy in the mathematics learning process. The method used is descriptive bibliometric analysis with the use of dimension databases that include research data for the last 10 years. The results of the analysis show that the peak of publications occurred in 2022 with 105 relevant publications.